Analisis Penerapan Metode PAIKEM GEMBROT dalam Pembelajaran Bahasa Arab di Era Pandemi - Wilda Rihlasyita Rihlasyita; Rina Dian Rahmawati (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
This paper discusses about the implementation of PAIKEM GEMBROT Method in Arabic Learning in the Pandemic Era. As we know that Learning Arabic Languange in the pandemic covid-19 have a challenge for both, teachers and also the students. Learning by using internet is a must for them. So that, the implementation of PAIKEM GEMBROT method is one of inovation that can do by the teacher to reach the purpose of learning. The Discussion of this paper focus on the explaining the implementation of PAIKEM GEMBROT method by using Language Games, especially fof the students of STAI Al-Yasini Pasuruan. This paper used descriptive method and the instrument of collecting the data are by using observation, interview and documentation. The result of this paper shows that the implementation of PAIKEM GEMBROT method by using Language Games is effective to improve the result of learning process for the students of Education Arabic Department in STAI Al-Yasini Pasuruan especially in pandemic era. Keywords: PAIKEM GEMBROT Method, Arabic Language Games, Pandemic Era